Performance Enhancement toward Developed Computer Vision Measurement Application for End Mill Cutting Tool - Chong, Bin Hong; Ibrahim, Rasidi (Research Progress in Mechanical and Manufacturing Engineering, 2022)
High mix low volume become mainstream trend recently among manufacturing due to the transform of consumption pattern especially during pandemic in order to maintain healthy cash flow. A rapid and flexible equipment especially in measurement required by quality control department of an end mill cutting tool manufacturer in order to enhance the productivity on daily output. Demand on design and develop a high degree of freedom computer vision measurement application is evident to overcome the tribulation of the department. In this research, a multi features developed computer vision measurement application will be the research object toward the performance during measurement and yet the enhancement will be carries out in order to increase the reliability of the measurement result output of the end mill cutting tool. The enhancements of the developed computer vision measurement application are mainly in program algorithm perspectives and the reliability of the measurement improved up to 80% in term of standard deviation or achieved below 1 micron repeatability for every measurement features. The root causes of unstable for the developed computer vision measurement application are concluded and recommendations are given in the end of this research.